Numerical Modeling and Optimization of Lead-Free Hybrid Double Perovskite Solar Cell by Using SCAPS-1D. (17th July 2021) - Hussain, Syed Sajjad; Riaz, Saira; Nowsherwan, Ghazi Aman; Jahangir, Khizer; Raza, Akram; Iqbal, Muhammad Javaid; Sadiq, Imran; Hussain, Syed Mutahir; Naseem, Shahzad
Abstract : The highest power conversion efficiency (PCE) for organic-inorganic perovskite solar cells based on lead is reported as 25.2% in 2019. Lead-based hybrid perovskite materials are used in several photovoltaics applications, but these are not highly favored due to the toxicity of lead and volatility of organic cations. On the other hand, hybrid lead-free double perovskite has no such harm. In this research study, SCAPS numerical simulation is utilized to evaluate and compare the results of perovskite solar cell based on double perovskite FA 2 BiCuI 6 and standard perovskite CH 3 NH 3 PbI 3 as an active layer. The results show that the power conversion efficiency obtained in the case of FA 2 BiCuI 6 is 24.98%, while in the case of CH 3 NH 3 PbI 3, it is reported as 26.42%. This indicates that the hybrid organic-inorganic double perovskite FA 2 BiCuI 6 has the ability to replace hybrid organic-inorganic perovskite CH 3 NH 3 PbI 3 to expand next-generation lead-free harmless materials for solar cell applications.